Response of Growth and Yield of Mint (Mentha spicata) Cuttings to Auxin and Composition of Planting Media - Eddy Triharyanto; Bambang Pujiasmanto; Pardono Pardono; Aisyah Taqiyyah Fa’izah (Agrotechnology Research Journal, 2023)
Consumption of herbal medicines by Indonesian people is increasing because of the price and ease of obtaining them. One of the main ingredients of herbal medicine is mint leaves because they contain tannin and flavonoid secondary metabolites. However, the generative mint plant is very slow and needs vegetative cuttings propagation. This study aims to examine the effect of auxin-type growth regulators and the composition of the growing media on the growth and yield of mint plant cuttings. This study used a complete randomized block design with two factors. The first factor was the auxin growth regulator with four levels: without growth regulator, IBA 500 ppm, IAA 500 ppm, NAA 500 ppm. The second factor was the composition of the planting medium with three levels, namely soil, husk charcoal, and goat manure 3:3:1; 3:2:2, and 3:1:3. Three repetitions were carried out. Auxin affects the number and area of leaves. Applying 500 ppm NAA encouraged the highest leaf growth, with the number of leaves at 163.38. Growth regulator NAA 500 ppm increased the number of leaves and leaf area of mint plants, i.e., by 0.01% and 1.16% compared to the control. The growing media composition affected the crown fresh weight, root biomass, and crown root ratio. The media composition of 3:3:1 produced a crown fresh weight of 41.07 g, and the media composition 3:3:3 produced the highest biomass of 5.97 g. The media composition 3:1:3 showed the highest root crown ratio, 2.69%. Auxin and the composition of the growing media synergistically promote the growth and yield of mint cuttings.